Magnetic fields in molecular clouds: limitations of the analysis of Zeeman observations - Brauer, Robert; Reißl, Stefan (Astronomy and astrophysics, 2017)
Context. Observations of Zeeman split spectral lines represent an important approach to derive the structure and strength of magnetic fields in molecular clouds. In contrast to the uncertainty of the spectral line observation itself, the uncertainty of the analysis method to derive the magnetic field strength from these observations has so far not been well characterized. Aims. We investigate the impact of several physical quantities on the uncertainty of the analysis method, which is used to derive the line-of-sight (LOS) magnetic field strength from Zeeman split spectral lines. These quantities are the density, temperature, velocity, and magnetic field strength. Methods. We simulated the Zeeman splitting of the 1665 MHz OH line with the 3D radiative transfer (RT) extension ZRAD. This extension is based on the line RT code Mol3D and has been developed for the POLArized RadIation Simulator POLARIS. Results. Observations of the OH Zeeman effect in typical molecular clouds are not significantly affected by the uncertainty of the analysis method. However, some observations obtained a magnetic field strength of more than ~300 μG, which may result in an uncertainty of the analysis method of > 10%. We derived an approximation to quantify the range of parameters in which the analysis method works accurately enough and provide factors to convert our results to other spectral lines and species as well. We applied these conversion factors to CN and found that observations of the CN Zeeman effect in typical molecular clouds are not significantly affected by the uncertainty of the analysis method. In addition, we found that the density has almost no impact on the uncertainty of the analysis method, unless it reaches values higher than those typically found in molecular clouds (nH ≫ 107 cm-3). Furthermore, the uncertainty of the analysis method increases if both the gas velocity and magnetic field show significant variations along the LOS. However, this increase should be small in Zeeman observations of most molecular clouds considering typical velocities of ~1 km s-1.
Published online 10 May 2017
Gesehen am 19.06.2018